Bibliometric approach to tracking the concept of international competitiveness - Olczyk, Magdalena (Journal of Business Economics and Management, 2016)
The main aim of paper is to identify the growth pattern in the international competitiveness literature, its core publications and key research domains on the basis of bibliometric data from the years 1945–2015. Citation data is collected from the ISI Web of Science Website, Scopus and Google Scholar, and analysed using HistCite, Pajek and VOSviewer software. Bibliometric indicators, network citation, key-route path methods and term co-occurrence methods are used. The results show that the theory of international competitiveness starts not from neoclassical theories of international trade, but from models of competition, even though competitiveness is mostly measured using trade/export performance. Krugman’s work on imperfect competitive markets and increasing returns of scale plays a most important role in knowledge diffusion on international competitiveness. The scientific development of analyzed concept is connected with six topics: trade performance, technology, liberalization, environmental regulations, location and productivity. These results give us a background for conducting practical analyses of international competitiveness, especially ones using synthetic indices.